Mapping Fuzzy Petri Net to Fuzzy Extended Markup Language - Zahra Masoudinezad; Ali Haroon Abadi; Mohammad Teshnehlab (Institute of Advanced Engineering and Science, 2013)
Use of model gives the knowledge and information about the phenomenon also eradicates the cost, the effort and the hazard of using the real phenomenon. Characteristics and concepts of Petri nets are in a way that makes it simple and strong to describe and study the information processing system; especially it is shown in those which are dealing with discrete, concurrent, distributed, parallel and indecisive events. Yet, due to Petri nets inability to face with systems working on obscure data and continues events, the interest to develop fundamental concept of Petri nets has been raised which is led to new style of presented model named